Work-family conflict in work groups: Social information processing, support, and demographic dissimilarity - BHAVE, Devasheesh P. (Institutional Knowledge at Singapore Management University, 2010)
We used social information processing theory to examine the effect of work-family conflict (WFC) at the work group level on individuals' experience of WFC. Consistent with hypotheses, results suggest that WFC at the work group level influences individual WFC over and above the shared work environment and job demands. It was also observed that work group support and demographic dissimilarity moderate this relationship. Moderator analyses suggest that work group social support buffers WFC for individuals but is also associated with a stronger effect of work group WFC on individuals' WFC. Moreover, the work group effect on individuals' WFC was shown to be stronger for individuals who were demographically dissimilar to the work group in terms of sex and number of dependents. The interpretations and implications of these findings are discussed.